Assessment of genetic diversity in Indian mustard [Brassica juncea (L.) Czern & Coss.] genotypes for yield and its component traits (Journal of Oilseed Brassica, 2025)
Genetic diversity analysis in 40 genotypes of Indian mustard [Brassica juncea (L.) Czern & Coss.] using Mahalanobis D2 statistics for 13 characters enabled grouping these 40 genotypes into 6 clusters. Cluster V was the largest comprised 11 genotypes followed by cluster IV consisting of 10 genotypes, cluster III with 7 genotypes whereas cluster I, II & VI with 4 genotypes each. It was observed that number of secondary branches/ plant, length of siliqua, number of primary branches, plant height, number of siliqua per plant and seeds per siliqua were the major contributors towards genetic divergence. The cluster IV had maximum intra cluster distance (2.815) while maximum inter cluster distance observed between cluster IV and I (6.346), suggesting that the genotypes constituted in these clusters may be used as parents for future hybridization programme in mustard.